Two-dimensional ferromagnetic single crystal Cr1-xVxI3 as well as preparation method and application thereof
The preparation of two-dimensional ferromagnetic Cr1-xVxI3 single crystals through doping and controlled chemical vapor transport addresses the size and yield limitations of existing van der Waals materials, enabling large, high-quality crystals for advanced device applications.
Patent Information
- Application Number
- CN202411285875.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
AI Technical Summary
Existing two-dimensional van der Waals materials face challenges with small single crystal size and limited yield, leading to a complicated and costly preparation process.
A two-dimensional ferromagnetic Cr1-xVxI3 single crystal is prepared by doping V into CrI3 using the chemical vapor transport method, controlling the temperature gradient and insulation times in a tube furnace to achieve large-sized and high-yield single crystals with uniform composition.
The method results in large-sized, high-quality Cr1-xVxI3 single crystals with strong magnetic anisotropy and unique topological magnetic structures, suitable for applications in van der Waals heterojunction devices.
Smart Images

Figure CN119177493A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of two-dimensional materials and preparation thereof, and in particular to a two-dimensional ferromagnetic Cr 1-x V x I3 single crystal and its preparation method and application. Background Art
[0002] Two-dimensional van der Waals materials have developed into a large family of metals, semiconductors, insulators, semimetals, and various topological materials with excellent magnetoelectric, optoelectronic and other properties. In particular, the discovery of magnetic two-dimensional van der Waals materials has provided opportunities for the development of low-power spintronic devices. In addition, two-dimensional van der Waals materials have smooth surfaces without dangling bonds, and can be stacked and assembled into van der Waals heterojunction devices by van der Waals forces, realizing more applications beyond traditional electronic and optoelectronic devices. With the discovery of two-dimensional intrinsic magnetic crystals, more functions are added to van der Waals heterostructure devices, providing more exciting opportunities for the application of breakthrough devices.
[0003] However, existing two-dimensional van der Waals materials suffer from small single crystal size and limited yield, which makes their preparation process complicated and costly.
[0004] To this end, the present invention provides a two-dimensional ferromagnetic Cr 1-x V x I3 single crystal and its preparation method and application. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a two-dimensional ferromagnetic Cr 1-x V x I3 single crystal and its preparation method and application. The present invention uses Cr single substance powder, V single substance powder and I single substance particles as raw materials, adopts chemical vapor transport method, makes V uniformly doped in CrI3, and partially replaces Cr position in CrI3, thereby breaking the lattice symmetry of CrI3, resulting in Cr 1-x V x The inherent reverse symmetry breaking in I3 produces a non-trivial topological magnetic structure, resulting in a two-dimensional magnetic Cr with a strange quantum state. 1-x V x I3 single crystal. In addition, the present invention can greatly improve the two-dimensional magnetic Cr by controlling the insulation time of the growth end of the tube furnace to be greater than the insulation time of the reaction end during the chemical vapor transport process. 1-x V x Size and yield of I3 single crystals.
[0006] A two-dimensional ferromagnetic Cr 1-x V x The I3 single crystal and its preparation method are realized by the following technical scheme:
[0007] The first object of the present invention is to provide a two-dimensional ferromagnetic Cr 1-x V x I3 single crystal, the two-dimensional ferromagnetic Cr 1-x V x I3 single crystal is based on CrI3, and V is introduced by doping to partially replace the Cr position in CrI3. Its chemical formula is Cr 1-x V x I3; wherein x is the doping molar percentage of V in the Cr position in CrI3, and the value range of x is 10% to 90%.
[0008] The second object of the present invention is to provide a two-dimensional ferromagnetic Cr 1-x V x The present invention is based on the advantages of chemical vapor transport method, which is simple to operate and can grow high-quality single crystals. The method is preferably used for preparation to achieve the growth of high-quality Cr 1-x V x The goal of I3 single crystal is achieved through the following steps:
[0009] Step 1, according to the chemical formula Cr 1-x V x According to the stoichiometric ratio in I3, corresponding masses of Cr single substance powder, V single substance powder and I single substance particles are weighed and mixed to obtain a mixed powder.
[0010] It should be noted that the present invention takes into account the need to uniformly incorporate V into the Cr lattice and ensure that the molar ratio of each element in the single crystal is consistent with the ratio when weighed, and preferably uses high-purity Cr powder, V powder and I particles as raw materials to achieve the goal of obtaining single crystals with uniform composition.
[0011] In order to ensure that the Cr single substance powder, V single substance powder and I single substance particles can be mixed evenly, so as to form a two-dimensional magnetic Cr with uniform composition in the subsequent 1-x V x I3 single crystal, in some preferred embodiments of the present invention, the Cr single substance powder, V single substance powder and I single substance particles are mixed by grinding, and the particle size of the mixed powder is 5μm to 20μm. For example, in some other preferred embodiments of the present invention, a mortar is used for grinding for 0.5h to 1.5h to mix the Cr single substance powder, V single substance powder and I single substance particles.
[0012] In order to facilitate the mixing of Cr single substance powder, V single substance powder and I single substance particles, in some preferred embodiments of the present invention, the particle size of the Cr single substance powder is 5 μm to 8 μm. In some other preferred embodiments of the present invention, the particle size of the V single substance powder is 15 μm to 20 μm.
[0013] Step 2, placing the mixed powder into a quartz tube, sealing it after evacuation, and then placing the sealed quartz tube in a tube furnace, raising the temperature of the reaction end of the tube furnace to 800°C to 900°C, and raising the temperature of the growth end of the tube furnace to 700°C to 800°C.
[0014] It should be noted that the present invention takes into account the factors of uniformly doping V single substance and ensuring that the molar ratio of each element in the single crystal meets the ratio when weighed, and raises the temperature of the reaction end of the tube furnace to 800℃~900℃, so that the transport agent I single substance particles are heated and volatilized at the high temperature end, and fully react with the Cr single substance powder and the V single substance powder in the temperature range to generate a gaseous intermediate product binary iodide, in which the I single substance particles serve as both a transport agent and a reactant. The temperature of the growth end of the tube furnace is raised to 700℃~800℃, so that the gaseous intermediate product is diffused and transported to the low temperature end under the action of the temperature gradient, and a reverse reversible reaction occurs at the low temperature end to generate the target product Cr 1-x V x I3 slowly nucleates and grows in the low temperature zone, thereby achieving the goal of obtaining single crystals with uniform composition and large size.
[0015] During the heating process, the temperature difference between the reaction end and the growth end of the tube furnace needs to be 80°C to 120°C to establish a temperature gradient so that the gas phase intermediate product can be transferred to the low temperature end for deposition and crystallization under the action of the temperature gradient.
[0016] It should be emphasized that in order to prevent the iodine in the mixed powder from forming a large amount of iodine vapor during the heating process, which may cause the quartz tube to rupture, in some preferred embodiments of the present invention, the heating rate of the reaction end of the tube furnace is 0.25°C / min to 0.28°C / min. Therefore, in some other preferred embodiments of the present invention, the heating rate of the growth end of the tube furnace is 0.22°C / min to 0.25°C / min.
[0017] Step 3, the reaction end of the tube furnace is kept at 800°C to 900°C for 9980min to 10180min and then cooled to room temperature, and the growth end of the tube furnace is kept at 700°C to 800°C for 10180min to 10380min and then cooled to room temperature, and the two-dimensional magnetic Cr is obtained at the growth end of the quartz tube. 1-x V x I3 single crystal.
[0018] It should be noted that in order to ensure the preparation of large-size and high-yield Cr 1-x V xI3, make the holding time of the growth end of the tube furnace longer than that of the reaction end, so that the crystal is formed slowly at the growth end, which helps to increase the grain size and reduce grain defects, thereby forming large-sized and high-quality Cr in the growth end. 1-x V x I3 single crystal target.
[0019] In order to ensure that the two-dimensional magnetic Cr 1-x V x I3 single crystal, in some preferred embodiments of the present invention, the difference in insulation time between the reaction end and the growth end of the tube furnace is 170min to 230min.
[0020] The third object of the present invention is to provide a two-dimensional ferromagnetic Cr 1-x V x Application of I3 single crystal in the preparation of van der Waals heterojunction devices.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses Cr single substance powder, V single substance powder and I single substance particles as raw materials, adopts chemical vapor transport method, makes V uniformly doped in CrI3, and partially replaces Cr position in CrI3, thereby breaking the lattice symmetry of CrI3, resulting in Cr 1-x V x The inherent reverse symmetry breaking in I3 produces a non-trivial topological magnetic structure, resulting in a two-dimensional magnetic Cr with a strange quantum state. 1-x V x I3 single crystal. In addition, the present invention can greatly improve the two-dimensional magnetic Cr by controlling the insulation time of the growth end of the tube furnace to be greater than the insulation time of the reaction end during the preparation process of the chemical vapor transport method. 1-x V x Size and yield of I3 single crystals.
[0023] The preparation method of the present invention is simple and easy to operate, and can be easily promoted for large-scale production and use. 1-x V x I3 single crystal has the characteristics of large size, high yield and high quality.
[0024] And the test shows that the two-dimensional magnetic Cr 1-x V x The block size of I3 single crystal can reach the centimeter level, and thin layers with smooth surface, micrometer size and nanometer thickness can be easily prepared by mechanical peeling. The magnetic property test results show that the two-dimensional magnetic Cr 1-x V xI3 single crystal has strong magnetic anisotropy, and the easy magnetic axis is out of plane. During the heating process, a phase transition from ferromagnetism to paramagnetism occurs near the Curie temperature. And the magneto-optical Kerr technique test shows that the two-dimensional ferromagnetic Cr 1-x V x There is an antisymmetric Kerr peak in the hysteresis loop of the I3 flake. Combined with theoretical calculations, it is determined that the Kerr peak originates from magnetic skyrmions, which is one of the manifestations of topological charge and is called the topological Kerr effect. This indicates that the two-dimensional magnetic Cr 1-x V x I3 single crystal is a ferromagnetic semiconductor material with a new type of spin order. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the process of preparing samples using the chemical vapor transport method in the present invention.
[0026] Figure 2 is the Cr in Example 1 0.8 V 0.2 Optical photograph of I3 single crystal.
[0027] Figure 3 is the Cr in Example 1 0.8 V 0.2 Scanning electron micrograph of an I3 single crystal.
[0028] Figure 4 is the Cr in Example 1 0.8 V 0.2 Elemental energy spectrum analysis of I3 single crystal.
[0029] Figure 5 is the Cr in Example 1 0.8 V 0.2 X-ray diffraction pattern of I3 single crystal.
[0030] Figure 6 is the Cr in Example 1 0.8 V 0.2 The curve of magnetization intensity of I3 single crystal changing with temperature.
[0031] Figure 7 is the Cr in Example 1 0.8 V 0.2 In-plane and out-of-plane hysteresis loops of I3 single crystal at 10K.
[0032] Figure 8 is the Cr in Example 1 0.8 V 0.2 Magneto-optical Kerr hysteresis loop of I3 single-crystalline nanosheet. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0034] Example 1
[0035] This embodiment provides a two-dimensional magnetic Cr 0.8 V 0.2 I3 single crystal, and it is prepared by the following steps:
[0036] Step 1, preparation of mixed powder:
[0037] Cr powder, V powder and I particles were weighed in a molar ratio of 0.8:0.2:3 to obtain a mixed powder.
[0038] Step 2, preparation and heating phase of chemical vapor transport process:
[0039] 1) The powders obtained above are mixed evenly and placed in a quartz tube, and the quartz tube is sealed after vacuuming.
[0040] 2) Place the sealed quartz tube horizontally in a tube furnace, and raise the temperature of the reaction end to 850°C and the temperature of the single crystal growth end to 750°C within 3000 min. Figure 1 .
[0041] Step 3, the insulation and cooling phases of the chemical vapor transport process:
[0042] The reaction end of the tube furnace was kept at 850℃ for 10080min and then naturally cooled to room temperature. The growth end of the tube furnace was kept at 750℃ for 10280min and then naturally cooled to room temperature. Large pieces of Cr were obtained at the growth end. 0.8 V 0.2 I3 single crystal, and the obtained Cr 0.8 V 0.2 The physical morphology of I3 single crystal is as follows Figure 2 shown.
[0043] Example 2
[0044] This embodiment provides a two-dimensional magnetic Cr 0.1 V 0.9 I3 single crystal, and it is prepared by the following steps:
[0045] Step 1, preparation of mixed powder:
[0046] Cr powder, V powder and I particles were weighed in a molar ratio of 0.1:0.9:3 to obtain a mixed powder.
[0047] Step 2, preparation and heating phase of chemical vapor transport process:
[0048] 1) The mixed powder obtained above is evenly placed in a quartz tube, and the quartz tube is sealed after vacuuming.
[0049] 2) Place the sealed quartz tube horizontally in a tube furnace, and raise the temperature of the reaction end to 900°C and the temperature of the single crystal growth end to 800°C within 3000 min. Figure 1 .
[0050] Step 3, the insulation and cooling phases of the chemical vapor transport process:
[0051] The reaction end of the tube furnace was kept at 900℃ for 9980min and then naturally cooled to room temperature. The growth end of the tube furnace was kept at 800℃ for 10180min and then naturally cooled to room temperature. Large pieces of Cr were obtained at the growth end. 0.1 V 0.9 I3 single crystal.
[0052] Example 3
[0053] This embodiment provides a two-dimensional magnetic Cr 0.9 V 0.1 I3 single crystal, and it is prepared by the following steps:
[0054] Step 1, preparation of mixed powder:
[0055] Cr powder, V powder and I particles were weighed in a molar ratio of 0.9:0.1:3 to obtain a mixed powder.
[0056] Step 2, preparation and heating phase of chemical vapor transport process:
[0057] 1) The powders obtained above are mixed evenly and placed in a quartz tube, and the quartz tube is sealed after vacuuming.
[0058] 2) Place the sealed quartz tube horizontally in a tube furnace, and raise the temperature of the reaction end to 800°C and the temperature of the single crystal growth end to 700°C within 3000 min. Figure 1 .
[0059] Step 3, the insulation and cooling phases of the chemical vapor transport process:
[0060] The reaction end of the tube furnace was kept at 800℃ for 10180min and then naturally cooled to room temperature. The growth end of the tube furnace was kept at 700℃ for 10380min and then naturally cooled to room temperature. Large pieces of Cr were obtained at the growth end. 0.9 V 0.1 I3 single crystal.
[0061] Comparative Example 1
[0062] This comparative example provides a two-dimensional magnetic Cr1-x V x I3 single crystal, and it is prepared by the following steps:
[0063] Step 1, preparation of mixed powder:
[0064] Cr powder, V powder and I particles were weighed in a molar ratio of 0.8:0.2:3 to obtain a mixed powder.
[0065] Step 2, preparation and heating phase of chemical vapor transport process:
[0066] 1) The powders obtained above are mixed evenly and placed in a quartz tube, and the quartz tube is sealed after vacuuming.
[0067] 2) Place the sealed quartz tube horizontally in a tube furnace, raise the temperature of the reaction end to 850°C and the temperature of the single crystal growth end to 750°C within 3000 min.
[0068] Step 3, the insulation and cooling phases of the chemical vapor transport process:
[0069] The reaction end of the tube furnace was kept at 850℃ for 10080min and then naturally cooled to room temperature. The growth end of the tube furnace was kept at 750℃ for 10080min and then naturally cooled to room temperature. Cr 1-x V x I3 single crystal.
[0070] That is, the difference between this comparative example and Example 1 is only that:
[0071] In this comparative example, the insulation time of the reaction end and the growth end is the same, that is, the insulation time difference between the reaction end and the growth end is 0 min, which exceeds the insulation time difference range of 170 min to 230 min specified in the present application.
[0072] The final single crystal sample obtained in this comparative example only nucleates and grows at the growth end, and the number and size of the obtained single crystal samples are much smaller than those in Example 1.
[0073] Comparative Example 2
[0074] This comparative example provides a two-dimensional magnetic Cr 1-x V x I3 single crystal, and it is prepared by the following steps:
[0075] Step 1, preparation of mixed powder:
[0076] Cr powder, V powder and I particles were weighed in a molar ratio of 0.8:0.2:3 to obtain a mixed powder.
[0077] Step 2, preparation and heating phase of chemical vapor transport process:
[0078] 1) The powders obtained above are mixed evenly and placed in a quartz tube, and the quartz tube is sealed after vacuuming.
[0079] 2) Place the sealed quartz tube horizontally in a tube furnace, raise the temperature of the reaction end to 850°C and the temperature of the single crystal growth end to 750°C within 3000 min.
[0080] Step 3, the insulation and cooling phases of the chemical vapor transport process:
[0081] The reaction end of the tube furnace was kept at 850℃ for 9980min and then naturally cooled to room temperature. The growth end of the tube furnace was kept at 750℃ for 10380min and then naturally cooled to room temperature. Less Cr with poor product quality was obtained at the growth end. 1-x V x I3 single crystal.
[0082] That is, the difference between this comparative example and Example 1 is only that:
[0083] The difference in insulation time between the reaction end and the growth end is 400 min, which exceeds the insulation time difference range of 170 min to 230 min specified in the present application.
[0084] During the heat preservation treatment process of this comparative example, the original reaction end temperature will be lower than the growth end, resulting in the inability of the reactants to fully generate volatile intermediates at the reaction end, thereby affecting the crystallization process at the growth end, and ultimately resulting in a decrease in the quality and size of the generated single crystal.
[0085] Experimental Section
[0086] (I) Scanning electron microscopy test
[0087] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 As an example, I3 single crystal was tested by scanning electron microscopy, and the test results are as follows Figure 3 shown.
[0088] Figure 3 is the Cr in Example 1 0.8 V 0.2 Scanning electron microscopy image of I3 single crystal shows that the Cr 0.8 V 0.2 The I3 single crystal has a smooth plane and layered structure, which can indicate that the Cr prepared in Example 1 of the present invention 0.8 V 0.2 I3 is a two-dimensional single crystal with a layered van der Waals structure.
[0089] (II) Energy spectrum test
[0090] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 Take I3 single crystal as an example, and perform element spectrum analysis on it. The test results are as follows: Figure 4 shown.
[0091] Figure 4 is the Cr in Example 1 0.8 V 0.2 The element spectrum analysis diagram of I3 single crystal shows that the Cr 1-x V x In the I3 single crystal, the molar ratio of Cr, V and I is 4:1:15, which indicates that Example 1 of the present invention successfully synthesized Cr with a molar ratio of 0.8:0.2:3. 0.8 V 0.2 This indicates that the present invention can adjust the molar ratio of Cr, V and I to obtain the desired two-dimensional ferromagnetic Cr with different V doping amounts. 1-x V x I3 single crystal.
[0092] (III) X-ray diffraction test
[0093] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 Taking I3 single crystal as an example, an X-ray diffraction test was performed on it, and the test results are as follows Figure 5 shown.
[0094] Figure 5 is the Cr in Example 1 0.8 V 0.2 From the X-ray diffraction pattern of I3 single crystal, it can be seen that the Cr 0.8 V 0.2 The I3 single crystal has good single crystal properties and is oriented in the (00l) direction, indicating that the Cr prepared in Example 1 0.8 V 0.2 I3 single crystals have a high degree of crystalline quality and a crystal orientation along the c-axis.
[0095] (IV) Curve of magnetization intensity changing with temperature
[0096] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 Taking I3 single crystal as an example, its magnetization intensity at different temperatures was tested, and the test results are summarized as follows Figure 6 shown.
[0097] The test method is: using a superconducting quantum interference device to measure the bulk Cr 0.8 V 0.2The in-plane and out-of-plane magnetization of I3 single crystals were measured. The magnetic field was 1000Oe, the temperature range was 10-300K, and a point was taken every 0.15K.
[0098] Figure 6 is the Cr in Example 1 0.8 V 0.2 The curve of the magnetization intensity of I3 single crystal changing with temperature is shown in Figure 2. Figure 6 It can be seen that the out-of-plane is the easy magnetization axis. With the increase of temperature, there is an obvious transition from ferromagnetism to paramagnetism, and the transition temperature is 63K.
[0099] (V) Hysteresis loop test
[0100] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 Taking I3 single crystal as an example, its hysteresis loop was tested, and the test results are as follows Figure 7 shown.
[0101] The test method is: using superconducting quantum interference device to test bulk Cr at 10K 0.8 V 0.2 The magnetization intensity of the I3 single crystal in the plane and out of the plane changes with the magnetic field. The magnetic field range is set to ±6T and the magnetic field interval is 400Oe.
[0102] Figure 7 is the Cr in Example 1 0.8 V 0.2 The in-plane and out-of-plane hysteresis loops of I3 single crystal at 10K are given by Figure 7 It can be seen that compared with the in-plane situation, the out-of-plane magnetization has a lower saturation field and a higher saturation magnetization, which further proves that the out-of-plane is the easy magnetization axis.
[0103] (VI) Magneto-optical Kerr hysteresis loop
[0104] The present invention uses the Cr obtained in Example 1 0.8 V 0.2 Taking I3 single crystal as an example, its magnetization intensity was tested using magneto-optical Kerr technique, and the test results are as follows: Figure 8 shown.
[0105] The test method is: 1-x V x After mechanical dissociation into layers, the I3 single crystal was transferred to a silicon dioxide substrate by dry transfer and then processed by PMM in a glove box. A After packaging, it is moved into the magneto-optical Kerr system and cooled to low temperature for testing. The test temperature is set to 10K and the magnetic field range is ±0.4T.
[0106] Figure 8 is the Cr in Example 10.8 V 0.2 The magneto-optical Kerr hysteresis loop of I3 single-crystal nanosheets is given by Figure 8 It can be seen that the magnetic properties of the thin layer sample are different from those of the bulk, that is, Cr 1-x V x There is an antisymmetric Kerr peak in the hysteresis loop of the I3 flake. Combined with theoretical calculations, it is determined that the Kerr peak originates from skyrmions, which is one of the manifestations of topological charge and is called the topological Kerr effect. This result has discovered a new type of ferromagnetic semiconductor material with spin order. This shows that the two-dimensional ferromagnetic Cr prepared by this invention 1-x V x I3 single crystal has excellent magnetoelectric, magneto-optical and other properties and can be used to prepare low-energy and high-density magnetic storage devices.
[0107] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A two-dimensional ferromagnetic Cr 1-x V x I3 single crystal, characterized in that Using CrI3 as the matrix, V is introduced by doping to partially replace the Cr position in CrI3, and the chemical formula is Cr 1-x V x I3; Wherein, x is the doping molar percentage of V in the Cr position in CrI3, and the value range of x is 10% to 90%.
2. A two-dimensional ferromagnetic Cr as claimed in claim 1 1-x V x The method for preparing I3 single crystal is characterized in that: The following steps are involved: According to the chemical formula Cr 1-x V x According to the stoichiometric ratio in I3, corresponding masses of Cr single substance powder, V single substance powder and I single substance particles are weighed and mixed to obtain a mixed powder; The mixed powder is placed in a quartz tube, which is sealed after vacuuming, and then the sealed quartz tube is placed in a tube furnace, the temperature of the reaction end of the tube furnace is raised to 800° C. to 900° C., and the temperature of the growth end of the tube furnace is raised to 700° C. to 800° C.; The reaction end of the tube furnace is kept at 800° C. to 900° C. for 9980 min to 10180 min and then cooled to room temperature, and the growth end of the tube furnace is kept at 700° C. to 800° C. for 10180 min to 10380 min and then cooled to room temperature, and the two-dimensional magnetic Cr is obtained at the growth end of the quartz tube. 1-x V x I3 single crystal.
3. The preparation method according to claim 2, characterized in that: The difference in insulation time between the reaction end and the growth end of the tube furnace is 170 min to 230 min.
4. The preparation method according to claim 2, characterized in that: The heating rate of the reaction end of the tube furnace is 0.25°C / min to 0.28°C / min.
5. The preparation method according to claim 2, characterized in that: The heating rate of the growth end of the tube furnace is 0.22° C. / min to 0.25° C. / min.
6. The preparation method according to claim 2, characterized in that: The temperature difference between the reaction end and the growth end of the tube furnace is 80°C to 120°C.
7. The preparation method according to claim 2, characterized in that: The Cr single substance powder, the V single substance powder and the I particles are mixed uniformly by grinding; The mixed powder is ground to a particle size of 5 μm to 20 μm.
8. The preparation method according to claim 2, characterized in that: The particle size of the Cr single substance powder is 5 μm to 8 μm.
9. The preparation method according to claim 2, characterized in that: The particle size of the V single substance powder is 15 μm to 20 μm.
10. A two-dimensional ferromagnetic Cr as claimed in claim 1 1-x V x Application of I3 single crystal in the preparation of low-energy and high-density magnetic storage devices.
